If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -6 = z + -8 Reorder the terms: -6 + 3z = z + -8 Reorder the terms: -6 + 3z = -8 + z Solving -6 + 3z = -8 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -6 + 3z + -1z = -8 + z + -1z Combine like terms: 3z + -1z = 2z -6 + 2z = -8 + z + -1z Combine like terms: z + -1z = 0 -6 + 2z = -8 + 0 -6 + 2z = -8 Add '6' to each side of the equation. -6 + 6 + 2z = -8 + 6 Combine like terms: -6 + 6 = 0 0 + 2z = -8 + 6 2z = -8 + 6 Combine like terms: -8 + 6 = -2 2z = -2 Divide each side by '2'. z = -1 Simplifying z = -1
| 9x-18=-20 | | 9z=5z+10 | | 4(6-3n)=96 | | 4y+7=3y+9graph | | 3+4x=8-5x | | 28+20x=-44 | | 12x+8=4x-12 | | 11a+2b+2c=200 | | 2p-4=9+2p | | 2p-4=9-2p | | 32=9a+3b+c | | 3y+4=7y+9 | | 2a-b=ac | | 4x+-8+12=-40 | | 8x+10=10X | | Y^2-3x-10=0 | | 40t+45= | | v=(3.14)(4)2 | | b=(3.14)(14)2 | | 4x-2(4-6)=-40 | | b=(3.14)(4)2 | | -2n-8(n-3)=84 | | x+21=2x+30 | | n+9=4-6 | | 3+3x^2-16x^3=0 | | y^4-13y^3+36=0 | | 5(z+6)=82z | | x+(x*.15)=6.88 | | 10(s-4)=-105 | | (xy+3z)(xy-3z)=9 | | 180=144x-9.6x^2 | | 3x+25=2x+65 |